The who, what, and how of teamwork research in medical operating rooms: A scoping review. Issue 3 (4th May 2023) - Raveendran, Lucshman; McGuire, Cailie S.; Gazmin, Stefanie; Beiko, Darren; Martin, Luc J.
ABSTRACT: Despite the importance of teamwork in the operating room (OR), teamwork can often be conflated with teamwork components (e.g., communication, cooperation). We reviewed the existing literature pertaining to OR teamwork to understand which teamwork components have been assessed. Following PRISMA guidelines for scoping reviews, 4, 233 peer-reviewed studies were identified using MEDLINE and Embase. Eighty-seven studies were included for synthesis and analysis. Using the episodic model of teamwork as an organizing framework, studies were grouped into the following teamwork categories: (a) transition processes (e.g., goal specification), (b) action processes (e.g., coordination), (c) interpersonal processes (e.g., conflict management), (d) emergent states (e.g., psychological safety), or (e) omnibus topics (a combination of higher-order teamwork processes). Results demonstrated that action processes were most frequently explored, followed by transition processes, omnibus topics, emergent states, and interpersonal processes. Although all studies were framed as investigations of teamwork, it is important to highlight that most explored only one or a few constructs under the overarching umbrella of teamwork. We advocate for enhanced specificity with descriptions of OR teamwork, reporting practices pertaining to interprofessional demographics and outcomes, and increased diversity in study design and surgery type to advance understanding of teamwork and its implications.